2015
DOI: 10.1007/s12020-015-0744-1
|View full text |Cite
|
Sign up to set email alerts
|

Rescue in vitro maturation (IVM) of immature oocytes in stimulated cycles in women with low functional ovarian reserve (LFOR)

Abstract: Rescue in vitro maturation (IVM) is currently not a routine procedure in association with in vitro fertilization (IVF). We compared in a prospectively cohort study of 10 patients with normal functional ovarian reserve (NFOR) and of 25 with low functional ovarian reserve (LFOR), defined by abnormally high FSH and/or abnormally low AMH levels), IVM dynamics of immature oocytes. Following controlled ovarian hyperstimulation in IVF cycles, only immature oocytes underwent rescue IVM (for up to 48 h). Oocyte maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Our initial fear of producing large numbers of immature oocytes was unfounded, as using IVM we obtained more good-quality embryos than in cycles with standard ovulation induction timing (16). Since women with LFOR usually produce only small embryo numbers, IVM in addition offers them proportionally better gains in transferable embryo numbers than women with normal FOR (17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our initial fear of producing large numbers of immature oocytes was unfounded, as using IVM we obtained more good-quality embryos than in cycles with standard ovulation induction timing (16). Since women with LFOR usually produce only small embryo numbers, IVM in addition offers them proportionally better gains in transferable embryo numbers than women with normal FOR (17).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the recognition that follicles increasingly luteinize prematurely with advancing age, over the last year we started to administer hCG triggers in women above age 43 at 16 mm lead follicle size and in older women with promising results as early as 14 mm (16). Immature oocytes undergo in vitro maturation (IVM), which we have demonstrated to be effective in increasing the embryo numbers available for transfer in women with LFOR (17).…”
Section: Ovarian Preparation and Stimulationmentioning
confidence: 99%
“…Rescue IVM produced 1.5 additional embryos for transfer in women with low functional ovarian reserve and 1.6 in patients with normal functional ovarian reserve (Lee et al, 2016). Pregnancy and delivery chances were also improved with rescue IVM in women with low functional ovarian reserve (Lee et al, 2016). Different time dynamics were noted between women with low functional ovarian reserve and those with normal functional ovarian reserve.…”
Section: Rescue Of Oocytes Which Have Failed To Mature In Stimulated mentioning
confidence: 97%
“…A prospective study demonstrated the utility of rescue IVM, concluding that it should become routine practice in women with low functional ovarian reserve (Lee et al, 2016). Rescue IVM produced 1.5 additional embryos for transfer in women with low functional ovarian reserve and 1.6 in patients with normal functional ovarian reserve (Lee et al, 2016). Pregnancy and delivery chances were also improved with rescue IVM in women with low functional ovarian reserve (Lee et al, 2016).…”
Section: Rescue Of Oocytes Which Have Failed To Mature In Stimulated mentioning
confidence: 99%
See 1 more Smart Citation